Analysis Of the Effect of Work Process Digitalization, Employee Experience, and Ethical Leadership on Employee Performance in Technology Start-Up Companies - Nugraha, Jefri Putri; Nurdiani, Tanti Widia; Abubakar, Faisal; Kamaluddin, Santrio; Suntoro, Bambang; Violin, Vivid (Yayasan Gema Bina Nusantara, 2025)
This study aims to analyze the influence of work process digitalization, employee experience, and ethical leadership on employee performance in technology start-up companies in Indonesia. In the digital era, start-up companies are required to continue to innovate and adapt quickly to technological changes, so the role of work process digitalization becomes increasingly crucial. In addition, individual work experience and ethical leadership are also believed to play an important role in driving employee performance. This study uses a quantitative approach with a survey method, involving 100 respondents who work in various technology start-up companies. The analysis technique used is Partial Least Square Structural Equation Modeling (PLS-SEM). The results of the study show that work process digitalization has a positive and significant effect on employee performance. Employee experience also shows a positive effect, although not as strong as the digitalization variable. Meanwhile, ethical leadership has the most significant influence in shaping employee behavior and work motivation. This finding strengthens the results of previous studies, which state that an ethical and digital work environment can drive employee productivity and loyalty. The implications of this study underline the importance of start-up companies adopting digital strategies and focusing on developing ethics-based leadership in their HR management.